MARKET RISK EFFECTS AND FINANCIAL PERFORMANCE OF LISTED BREWERY FIRMS IN NIGERIA (Journal of Global Accounting, 2023)
In Nigeria today, many firms were noted to have closed down in recent time and the attendant effects on national economic growth as workers were massively disengaged due to failed business problem. The broad objective of the study is to determine the effect of market risk on financial performance of listed brewery firms in Nigeria. Specifically, the effects of inflation rate, exchange rate, interest rate, tax rate and liquidity risk on asset turnover of listed Brewery firms in Nigeria. The study used ex-post facto research design. The population of the study was made up of all the five (5) listed breweries companies on the Nigerian Exchange Group. The study used purposive sampling technique to sample the four (4) brewery firms. Secondary data were extracted from Central Bank of Nigeria (CBN) Statistical Bulletin (2021) and audited financial statements and annual reports of the individual brewery firms from 2012 to 2021. The regression estimates were estimated using Ordinary Least Square regression and Generalized Least Square regression, at 5% level of significance. The results showed that: inflation rate and tax rate have a positive but non-significant effect on asset turnover of quoted breweries firms in Nigeria; interest rate has a negative and non-significant effect on asset turnover of quoted breweries firms in Nigeria; exchange rate has a negative but significant effect on asset turnover of quoted breweries firms in Nigeria and liquidity risk has a positive and significant effect on asset turnover of quoted breweries firms in Nigeria. The study concluded that a sub-optimal balance between liquidity and profitability trade-offs will result in a negative influence on the financial performance of the firm. In order to help breweries firms boost their performance, the researcher recommends that the cost of credit facilities should be reviewed downwards to enable smooth repayment and increase in the demand for loans by breweries firms to enable them grow their businesses which will in effect have positive effect in the economy
Keywords: Asset Turnover; Exchange Rate; Financial Performance; Inflation Rate; Interest Rate; Liquidity Risk; Market Risk; Tax Rate